(untitled) (Applied Biological Research, 2010)
A field experiment was conducted at Research orchard, Division of Fruit Science, FOA, SKUAST-J, Udheywalla, Jammu in a randomized block design to study the effect of green leafy manure of subabul (Leucaena leucocephala) integrated with urea and biofertilizer (Azotobacter sp.) on growth, yield and fruit quality of strawberry cv. ‘Chandler’ during 2006 and 2007. The application of 25% nitrogen (N) through subabul + 75% N in the form of urea augmented with biofertilizer resulted in maximum plant height (20.9 cm), plant spread (27.8 cm), leaf area (70.0 cm2), fruit size (38.4 x 28.9 mm), TSS (6.83° Brix), total sugars (4.85%), fruit weight (16.9 g), achene number fruit-1 (365.8) and yield (385.2 q ha-1). The results were, however, at par with the treatment where 50% N was applied through subabul + 50% N as urea augmented with biofertilizer. The present study revealed that in order to achieve comparable growth, yield and improved fruit quality as obtained with the use of recommended N doze through urea, the 50% N requirement could be replaced through subabul augmented with biofertilizer (Azotobacter).